Behaviour of stub columns with initial crack defects under axial compression. (June 2021) - Qiao, Huiyun; Pan, Jiahui; Chen, Yu; Pan, Jike
Abstract: An experimental investigation was conducted to evaluate the axial compressive behaviour of circular hollow section (CHS) stub columns with initial crack defects. A total of 96 specimens – 12 stub columns with one crack, 48 stub columns with two cracks, and 36 stub columns with three cracks – were tested under axial compression loading. The failure modes, load-carrying capacities, overall deflections, and strain intensities of all the specimens were examined. The design parameters were the tube thickness, long crack length, short crack length, crack spacing, and crack number. Additionally, a finite-element analysis was performed using the verified models in combination with the experimental data to evaluate the effects of the main influential factors. The initial cracks formed in the circular thin-walled stub columns accelerated the local buckling and changed both the bearing capacity and deformation capacity. The ultimate loads of the stub columns increased with the tube thickness, decreased slightly with an increase in the long crack length, and decreased with an increase in the crack spacing. The effects of the short crack length and crack number on the bearing capacity were complex and were coupled with the tube thickness. An adjustment coefficient was introduced into the predictive formula to estimate the ultimate bearing capacity. Through this, the ultimate bearing capacity can be accurately predicted. Highlights: Tests conducted on circular hollow section (CHS) tubes with initial crack defects. Specimens include various tube thickness, fracture length, fracture spacing. Various buckling and failure modes occur for the tubes with initial cracks. Initial cracks accelerate the local buckling and change the bearing capacity. Introduce adjustment factor into predictive formula to predict ultimate loading.